EFEKTIVITAS PENERAPAN METODE PEMBELAJARAN STUDENT TEAMS ACHIEVEMENT DIVISIONS DAN TEAM ASSISTED INDIVIDUALIZATION PADA MATERI REGRESI LINIER - Wulansari, Andhita Dessy (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2014)
Abstract; in general, learning statistics in class do not working at all, active lecturer predominate and student tend to passive as good hearer. Conventional study like this, make student only memorizing and working procedure without comprehend concept in fact. According to Hudojo, "With cooperative learn method give a chance to its student to develop themselves". Of course not all of cooperative learn method can be applied, should be selected as same as the field condition. This research, cooperative learn method of TAI (Team Assisted Individualization) and STAD (Student Teams Achievement Divisions) selected to be applied. Aim of this research is to compare applying effectiveness empirically of cooperative learn method between TAI, STAD and conventional through result statistics 2 of regression linear, grade 5th student of STAIN Ponorogo year of academic 2013 / 2014. According to data analysis using of One Way ANOVA statistics method, concluded that, there is difference result, learn statistics 2 of regression linear between class using learning method TAI, STAD and conventional. Where learning method TAI more effective than STAD and conventional; and STAD more effective if compared to conventional learning method.ÙÙØ®Øµ: ÙØ§Ù ØªØ¯Ø±ÙØ³ ÙØ§Ø¯Ø© Ø§ÙØ§ØØµØ§Ø¦ÙØ§Øª âØ¹Ø§ÙØ©- ÙØ§ ÙØ³ÙØ± Ø³ÙØ±Ø§ ÙØªÙØ§Ø²ÙØ§Ø ÙØ£Ù Ø§ÙÙØ¯Ø±Ø³ ÙÙ Ø§ÙÙÙÙÙÙ ÙØ§ÙÙØ§Ø¹Ù ÙØ§ÙØ·ÙØ§Ø¨ ØµØ§ÙØªÙÙ. Ø£Ø¯Ù ÙØ°Ø§ Ø§ÙÙÙØ¹ ÙÙ Ø§ÙØªØ¯Ø±ÙØ³ Ø¥ÙÙ Ø£Ù ÙØÙØ¸ Ø§ÙØ·ÙØ§Ø¨ ÙÙØ¹ÙÙÙÙ Ø±Ø³ÙÙØ§ ÙÙØ§ ÙÙÙÙÙÙ ØÙÙÙØ© Ø§ÙÙØ¸Ø±ÙØ§Øª. ÙØ±Ù ÙÙØ¯ÙØ¬Ù Ø£Ù ØªØ·Ø¨ÙÙ Ø·Ø±ÙÙØ© Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ§Ø´ØªØ±Ø§ÙÙ ÙØ¹Ø·Ù Ø§ÙØ·ÙØ§Ø¨ Ø§ÙÙØ±ØµØ© Ø§ÙÙØ§Ø³Ø¹Ø© ÙÙØªÙÙÙØ© Ø§ÙØ°Ø§ØªÙØ©. ÙØ·Ø¨Ø¹Ø§ Ø£Ù Ø¬ÙÙØ¹ Ø£ÙÙØ§Ø¹ Ø§ÙØªØ¹ÙÙ Ø§ÙØ£Ø´ØªØ±Ø§ÙÙ ÙØ§ ÙÙÙÙ ØªØ·Ø¨ÙÙÙØ§Ø Ø¨Ù ÙØ§Ø¨Ø¯ ÙÙ Ø§Ø®ØªÙØ§Ø± Ø§ÙØ£ÙØ³Ø¨ ÙÙÙØ§ Ø¨Ø§ÙÙØ§ÙØ¹. ÙØ®ØªØ§Ø± ÙØ°Ø§ Ø§ÙØ¨ØØ« ØªØ·Ø¨ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ§Ø´ØªØ±Ø§ÙÙ ÙÙØ¹ TAI (Team Assited Individualization) Â Ù STAD (Student Team Achievement Division) Â Â . ÙØ£ÙØ¯Ø§Ù ÙØ°Ø§ Ø§ÙØ¨ØØ« ÙÙ Ø§ÙÙÙØ§Ø±ÙØ© ÙØ§ÙØ¹ÙØ§ Ø¨ÙÙ ØªØ·Ø¨ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ§Ø´ØªØ±Ø§ÙÙ ÙÙØ¹ TAI AND STAD Â ÙØ§ÙØªÙÙÙØ¯ÙØ Ø¹Ø¨Ø± ÙØªØ§Ø¦Ø¬ ØªØ¹ÙÙ Ø§ÙØ§ØØµØ§Ø¦ÙØ§Øª (2) ÙØ§Ø¯Ø© REGRESI LINIER Â ÙØ¯Ù Ø·ÙØ§Ø¨ Ø§ÙØ¬Ø§ÙØ¹Ø© Ø§ÙØ¥Ø³ÙØ§ÙÙØ© Ø§ÙØÙÙÙÙØ© ÙÙÙÙØ±ÙØºÙ Ø§ÙÙØ³ØªÙÙ Ø§ÙØ®Ø§ÙØ³ Ø§ÙØ¹Ø§Ù Ø§ÙØ¯Ø±Ø§Ø³Ù 2013/2014 . Ø§Ø¹ØªÙØ§Ø¯Ø§ Ø¹ÙÙ ØªØÙÙÙ Ø§ÙØ¨ÙØ§ÙØ§Øª Ø¨Ø§Ø³ØªØ®Ø¯Ø§Ù Ø·Ø±ÙÙØ© Ø§ØØµØ§Ø¦ÙØ© One Way ANOVA Â ÙØ³ØªÙØªØ¬ ÙÙÙØ§ ÙØªØ§Ø¦Ø¬ Ø£Ù ÙÙØ§Ù ÙØ±Ù ÙÙ ÙØªØ§Ø¦Ø¬ ØªØ¹ÙÙ ÙØ§Ø¯Ø© Ø§ÙØ§ØØµØ§Ø¦ÙØ§Øª (2) ÙÙ ÙØ§Ø¯Ø© regresi linier Ø¨ÙÙ Ø§ÙØµÙ Ø§ÙÙØ³ØªØ®Ø¯Ù Ø·Ø±ÙÙØ© Ø§ÙØªØ¹ÙÙÙ TAI, STAD Â ÙØ§ÙØ·Ø±ÙÙØ© Ø§ÙØªÙÙÙØ¯ÙØ©. ÙØªÙÙÙ Ø·Ø±ÙÙØ© TAI Ø£ÙØ«Ø± ÙØ¹Ø§ÙØ§ Ø¨Ø§ÙÙØ³Ø¨Ø© Ø¥ÙÙ Ø·Ø±ÙÙØ© STAD Â ÙØ§ÙØ·Ø±ÙÙØ© Ø§ÙØªÙÙÙØ¯ÙØ© Ø ÙØ·Ø±ÙÙØ© STAD Â Ø£ÙØ«Ø± ÙØ¹Ø§ÙØ§ Ø¨Ø§ÙÙØ³Ø¨Ø© Ø¥ÙÙ Ø§ÙØ·Ø±ÙÙØ© Ø§ÙØªÙÙÙØ¯ÙØ©.Keywords: Efektivitas, TAI, STAD, Statistika